Periodized strength training for sprint kayaking/canoeing - Fekete, M. (Strength and Conditioning Journal, 1998)
The ultimate goal of strength training and conditioning for sprint kayaking/canoeing is to elevate the athlete's overall capacity through a properly structured and periodized strength training program to a level where he or she can produce consistently high power output. This capacity is called speed endurance. Theoretical considerations and practical experience confirm that in sprint flatwater kayaking/ canoeing: 1. Strength is the basic quality that provides the necessary foundation and influences the performance of others. 2. The best method for effectively structuring and manipulating strength training and conditioning in a goal oriented manner is periodization. It allows for planned, optimal, and timely conversion/ translation of gains achieved in one dimension of strength into qualities and further gains in another dimension. 3. The most effective strength training modality for optimal sequencing and integration of movements is freeweight training. 4. In order to maintain specific strength gains and high performance capacity, strength training and conditioning must be an integral part of the annual plan.